2022
DOI: 10.1177/01708406221077786
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Tekhnē: Configuring processes and politics through craft

Abstract: In this paper we investigate how craft as tekhnē configures organizations and their politics by exploring the relations of technology and organization. Through a two-year ethnographic study of remote craft villages in Vietnam, we consider how political concerns are mobilized, distributed and materialized through craft. Defining craft as a process of organizing that often involves mundane objects, but also sits at the centre of political concerns, we are interested in understanding how craft as tekhnē is realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Is it possible to imagine clothing production in a different way, one that does not depend on technologies reproducing the core ethical and political concerns at stake here? Gasparin et al (2020) suggested "slow design" as an imaginary solution to disrupt the anthropocentric modes of reasoning and imagine forms of organizing with nonhumans (see also Gasparin & Neyland, 2022). From this view, clothing production would respect the ecological cycles of nonhumans involved and rely on communal artisanal production.…”
Section: Thinking With Becoming Naturecultural: Re-visiting Anthropoc...mentioning
confidence: 99%
“…Is it possible to imagine clothing production in a different way, one that does not depend on technologies reproducing the core ethical and political concerns at stake here? Gasparin et al (2020) suggested "slow design" as an imaginary solution to disrupt the anthropocentric modes of reasoning and imagine forms of organizing with nonhumans (see also Gasparin & Neyland, 2022). From this view, clothing production would respect the ecological cycles of nonhumans involved and rely on communal artisanal production.…”
Section: Thinking With Becoming Naturecultural: Re-visiting Anthropoc...mentioning
confidence: 99%
“…In line with this, waiting time is likely to be utilised and experienced in divergent ways depending on the prevailing temporal structures within which it arises (Gasparini, 1995). Perhaps the most 'extreme cases' across which the experience of waiting might be contrasted are fast-paced knowledge work on the one hand (McGivern et al, 2018) and craft work (Gasparin & Neyland, 2022) on the other.…”
Section: Waiting In the Context Of Temporal Structuresmentioning
confidence: 99%